Planktonic ciliates from an oligotrophic South Andean lake, Morenito Lake (Patagonia, Argentina) - B. E. MODENUTTI (Brazilian Journal of Biology)
In this contribution we have studied the planktonic ciliates from Morenito Lake, an oligotrophic lake situated in the South Andes of Argentina. Six species that are new records for South America or Argentina are described and illustrated. Besides, population dynamics of the ciliate species were studied during a spring--summer period. Strobilidium lacustris and Balanion planctonicum were the most abundant species, showing a maximum in mid summer. Paradileptus elephantinus was present all over the period while Urotricha furcata was observed in late summer samples. Strobilidium lacustris and S. humile were found to be occasional species during the studied period. The recorded ciliate assemblage with oligotrichs and prostomates as dominant indicate the oligotrophic condition of the lake.